Analisa Tingkat Keselamatan Lalu Lintas Pada Persimpangan Dengan Metode Traffic Conflict Technique (TCT) - Suhadi, Imam; Mahda Rangkuti, Nuril (JCEBT (JOURNAL OF CIVIL ENGINEERING, BUILDING AND TRANSPORTATION), 2019)
Teransportasi is the most important means in a country, the development or absence of a country can be measured from the progress teransportasi existing in a conutry, the problems that many occur in Indonesia is a high traffic accident level, especially at the intersections of every road in Indonesia.Accidents are accidental or unexpected events that result in death, injury, or damage to objects. The outline of the accident is caused by four factors, namely human, vehicle, road and environment.TRAFFIC CONFLICT TECHNIQUE (TCT) is a method of observation conducted by collecting accidents that almost happened and see the pettern of the occurrence of accidents. Traffic Conflict Technique (TCT) developed by Departeman of traffic planning and engineering di Lund University di Swedia. Time to Accident (TA) is the time left since evasive action is done until the time of the collision if the road users do not change the speed of the vehicle and does not change the direction of the speed of the vehicle. The TA value is calculated based on the estimated distance (D) and vehicle speed (V) obtained from the survey results.After doing research with TCT method, it is found that the location of the research has the potential to couse an accident.In other words, this method can be used to improve the safety and comfort of road users, can provide a picture of the point of conflict at the intersection of a potential cause of accidents.